Isolation and characterisation of dominant acetic acid bacteria and yeast isolated from Kombucha samples at point of sale in New Zealand - Boying Wang (Current Research in Food Science, 2022)
The demand for Kombucha, a sparkling sugared tea beverage fermented by a symbiotic culture of acetic acid bacteria (AAB) and yeast is increasing worldwide. Despite the popularity of the beverage which is mainly due to its perceived health benefits and appealing sensory properties, the microbial composition of the products at the time of consumption is unknown. Such information is important to both manufacturers and consumers. Therefore, this study characterised the dominant AAB and yeast present in six commercial Kombucha samples sold in New Zealand which comprised of three domestic and three imported samples. Acetic acid bacteria and yeast were isolated from the Kombucha samples using glucose yeast extract peptone mannitol (GYPM) and yeast extract glucose chloramphenicol (YGC) media, respectively. Phenotypic and taxonomic identification of AAB and yeast were achieved by morphological and biochemical characterisation, followed by sequence analysis of ribosomal RNA genes (16S rRNA for AAB and 26S rRNA for yeast). Viable AAB and yeast were only found in domestically produced Kombucha samples and not in the imported products. The dominant AAB species were identified as Acetobacter musti and Gluconobacter potus. The yeast isolates belonged to Dekkera bruxelensis, Schizosaccharomyces pombes, Hanseniaspora valbyensis, Brettanomyces anamalus, Pichia kudriavzevii, Starmerella vitis and Saccharomyces cerevisiae. The yeast communities were more complex and variable than the AAB communities in the analysed Kombucha samples.